Jews of Iran a photographic chronicle - Sarbakhshian, Hassan, 1968-; Sternfeld, Lior B., 1979-; Vahidmanesh, Parvaneh, 1980- (Dimyonot (University Park, Pa.), 2022)
"A photographic exploration of life in the Jewish communities of Iran"--